A Cross-Sectional Evaluation of Knowledge of Medicine Safety and Frequency of Reading Medication Leaflets and Its Predictors – Insights From Saudi Adults in Riyadh, Saudi Arabia [Corrigendum] - Alghamdi A; Qadhi OA; Syed W; Samarkandi OA; Basil A Al-Rawi M (International Journal of General Medicine, 2025)
Alghamdi A, Qadhi OA, Syed W, Samarkandi OA, Basil A Al-Rawi M. Int J Gen Med. 2024;17:175—186. The authors have advised affiliation 1 on page 175 is incorrect. The correct affiliation should read “1Department of Community and Mental Health, College of Nursing, King Saud University, Riyadh, 11451, Saudi Arabia”. The authors apologize for this error.